The effect of oral creatine supplementation on one hour cycling performance and metabolism - Bellinger, Brett (MRC/UCT RU for Exercise and Sport Medicine, 2017)
The effect of oral creatine (Cr) supplementation with 20 g/day for 7 days on one-hour cycling performance and metabolism was investigated in a double-blind placebo controlled study. Twenty endurance-trained male cyclists volunteered for the study that was approved by the University of Cape Town ethics committee. The subjects' peak sustained power output was measured and they underwent a familiarization one-hour cycle on a cycle ergometer. Five days later subjects had a muscle biopsy and an indwelling cannula was inserted into a forearm vein before performing a maximal one-hour cycle (T1) during which blood samples were taken at regular intervals. Following the cycle, the subjects each received either Cr or placebo tablets to be ingested four times per day for the following week. After the loading week the subjects again reported to the laboratory, had a muscle biopsy and underwent and the same test routine (T2) with blood sampling as the previous week. Resting muscle total Cr measured by HPLC increased significantly (p<0.001) in the Cr group from 123.0 ± 3.8 mmol/kg dry wt to 159.8 ± 7.9 mmol/ kg dry wt, but was unchanged in the placebo group. The extent of Cr loading was not related to baseline Cr levels (r=0.46, NS). No differences were noted in the resting levels of adenine nucleotides in either group. Analyses of the plasma samples indicated no change in plasma lactate concentration, but a significant lowering of indicators of adenine nucleotide degradation including concentrations of plasma ammonia (p<0.05) and hypoxanthine (p<0.01) in the Cr group from T1 to T2. Plasma urate concentration was significantly lowered (p<0.01) from T1 to T2 but there were no differences between groups. Cr supplementation did not significantly improve performance in the one-hour trial (Cr group: 39.1 ± 0.9 km vs 39.8 ± 0.8 km and placebo group: 39.3 ± 0.8 km vs 39.2 ± 1.1 km). We hypothesised that Cr supplementation affects the purine nucleotide cycle through improved maintenance of low intracellular ADP during exercise as a result of enhanced efficiency of the Cr-PCr shuttle. Cr supplementation had no effect on lactate and carbohydrate metabolism and did not improve performance significantly during a one-hour cycle trial.